Playing by the rules sport, society, and the state - Wilson, John (Wayne State Univ. Press, 1994)
Sport, while it has its origins in the love of play and the desire to be entertained and diverted, is a social institution with important political, economic, and social consequences. Playing by the Rules describes how the relation between sport and the state has developed over the last one hundred years, and how, largely by indirection and accident, a public policy with respect to sport has emerged. Apart from the debate as to whether sport and politics should mix in the first place, John Wilson considers the process whereby sport has become a public policy domain, just like energy, health, transportation and agriculture. He argues that while all modern societies have evolved both sports complexes and extensive states, Americans have developed their own unique kind of relationship. This relationship grants considerable freedom for commercialized sports to develop, at the expense of more state-administered forms
Keywords: Sociale aspecten; Sport; Sports - Aspect social - États-Unis; Sports - Politique gouvernementale - États-Unis; Gesellschaft; Sports and state -- United States; Sports -- Social aspects -- United States; Wettbewerbspolitik; Sportsoziologie; Sportpolitik; Staat; USA